The Role of the Government of Indonesia in Handling Cases of Sexual Violence Against Women. - Ekklesia Hulahi; Umi Kulsum; Fitriani Fitriani; Dian Eka Rahmawati; Rahmawati Husein (Journal of Governance, 2022)
The purpose of this research is to see how the role of the Indonesian government in handling cases of sexual violence against women. The concepts used are the role and handling of the state and violence and protection of women. The method used is a qualitative approach to data analysis of cases of sexual violence taken from Komnas Perempuan data. The news media analyzed using NVivo 12 Plus software as an easy-to-use application. This study indicates that three factors become obstacles in handling cases of sexual violence, namely legal factors, fear, and inadequate protection. Because sexual violence against women is usually unresolved, resolve by paying a certain amount of money, marrying the perpetrator, imprisoning the perpetrator, and even making peace with the family. At the same time, the state's role is vital in handling cases of sexual violence through legal protection and influencing the justice of all citizens. But in fact, the data obtained shows that the handling and legal protection is still not adequate; women still experience sexual violence. The State of Indonesia uses various ways to handle cases of sexual violence with laws made on the Elimination of Domestic Violence or the Elimination of Sexual Violence. However, this does not become the basis for stopping sexual violence crimes in Indonesia.